A Communication Framework in Multiagent System for Islanded Microgrid - Hak-Man Kim; Yujin Lim (International Journal of Distributed Sensor Networks)
Microgrids are integrated energy systems consisting of interconnected loads and distributed energy sources which as a system can operate in parallel with the grid or in an island mode. By fault occurrence in the connected power system or geographical isolation, microgrids operate in the islanded mode. In the islanded mode, microgrids should be operated to meet a power balance between supply and demand without power trade. In recent years, multiagent systems have been proposed to provide intelligent energy control and management systems in microgrids. In this paper, we design a communication framework to control and operate distributed sources and loads in the islanded microgrids. The framework reliably delivers microgrid control frame between agents by employing wireless mesh network as an advanced topology of the wireless sensor network. From results of experiments, we show that our framework outperforms other conventional one, with respect to the rate of success on the transmission of frames among agents.